Glycosyltransferases: glycoengineers in human milk oligosaccharide synthesis and manufacturing - Slater, Alanna S.; McDonald, Andrew G.; Hickey, Rita M.; Davey, Gavin P. (Frontiers in Molecular Biosciences, 2025)
Human milk oligosaccharides (HMOs) are a diverse group of complex carbohydrates that play crucial roles in infant health, promoting a beneficial gut microbiota, modulating immune responses, and protecting against pathogens. Central to the synthesis of HMOs are glycosyltransferases, a specialized class of enzymes that catalyse the transfer of sugar moieties to form the complex glycan structures characteristic of HMOs. This review provides an in-depth analysis of glycosyltransferases, beginning with their classification based on structural and functional characteristics. The catalytic activity of these enzymes is explored, highlighting the mechanisms by which they facilitate the precise addition of monosaccharides in HMO biosynthesis. Structural insights into glycosyltransferases are also discussed, shedding light on how their conformational features enable specific glycosidic bond formations. This review maps out the key biosynthetic pathways involved in HMO production, including the synthesis of lactose, and subsequent fucosylation and sialylation processes, all of which are intricately regulated by glycosyltransferases. Industrial methods for HMO synthesis, including chemical, enzymatic, and microbial approaches, are examined, emphasizing the role of glycosyltransferases in these processes. Finally, the review discusses future directions in glycosyltransferase research, particularly in enhancing the efficiency of HMO synthesis and developing advanced analytical techniques to better understand the structural complexity and biological functions of HMOs.